2018
DOI: 10.1177/0961203318799188
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of early infectious and noninfectious complications in systemic lupus erythematosus patients undergoing major surgery

Abstract: Background We aimed to identify risk factors for early complications in systemic lupus erythematosus (SLE) patients undergoing major surgery. Methods We conducted a retrospective comparative cohort study including patients with SLE undergoing major surgery, and non-SLE patients matched 1:1. Main outcomes were development of infectious and noninfectious complications, and 30-day postoperative mortality. Results A total of 382 patients (191 SLE and 191 non-SLE) were included. Postoperative complications occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Steroids, DMARDs and biologic agents have been used widely for the treatment of major organ involvement in SLE. 15 However, it has been reported that the use of these drugs may carry significant risks in major surgery, including THA. 16 In the present study, we did not find that the use of steroid or DMARDs could increase the risk of complications after THA, but the use of DMARDs, especially tacrolimus, was associated with a higher risk of complications in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids, DMARDs and biologic agents have been used widely for the treatment of major organ involvement in SLE. 15 However, it has been reported that the use of these drugs may carry significant risks in major surgery, including THA. 16 In the present study, we did not find that the use of steroid or DMARDs could increase the risk of complications after THA, but the use of DMARDs, especially tacrolimus, was associated with a higher risk of complications in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to concerns about perioperative acute coronary events and anticoagulant and antiplate therapy therapy, non-operative treatment is often preferred for patients with intestinal perforation complicated with septic shock with CHD. Although SLE patients present higher frequency of postoperative complications and mortality compared with non-SLE patients (28), there were more patients with intestinal perforation combined with septic shock combined with SLE in the operative group. The reason for above phenomenon may be that SLE is an autoimmune disease, and patients with SLE with septic shock have a low chance of self-healing, which is likely to lead to more positive treatment.…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that SLE patients have increased risk of postoperative complications after major surgery, those mostly results in an increased rate of bleeding and infections, especially during hospitalization. Such studies concern major orthopedic surgery, because these patients are often affected by arthritis and they often undergo hips or knee arthroplasty [26] , [27] . Post-operative course in maxillofacial surgery has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, postoperative course might trigger SLE in these kinds of patients because of the increasing secretion of inflammatory cytokines. [27] .…”
Section: Discussionmentioning
confidence: 99%